A novel detection method of spray droplet distribution based on LIDARs - Yongjun, Zheng; Shenghui, Yang; Lan, Yubin; Hoffmann, Clint; Chunjiang, Zhao; Liping, Chen; Xingxing, Liu; Yu, Tan (International Journal of Agricultural and Biological Engineering, 2017)
During the process of plant protection in agriculture, the distribution and deposition of droplets or fog fields could directly influence the effectiveness and efficiency of spray. The traditional method of measurement of the distribution of droplets mainly used water sensitive papers, glass containers or flour to collect data and inverse results, while a new method of measurement based on the principle of reflection of LIDAR was presented. Droplets were the major targets of the study, and four important algorithms were primarily developed, including the recognition and extraction of targets, the superposition in time-domain, the calculation of effective ranges of distribution, and the development of 3D distribution models. Combined with these algorithms, in order to eliminate the environmental noise, the methods of Fuzzy Environment Matching and Secondary Filter were created and utilized. Meanwhile, the statistics was used for analysis of the duration of scanning as well as computation of the distribution, with enough datasets but the minimum length of time. The results of the experiments showed that the relative error of measurement was less than 7% and Relative Standard Deviation was less than 16%, compared with the values of manual measurement. Furthermore, the 3D models were accurate and clarified in the wind-tunnel experiment. The completed system based on this method could adapt to the requirements of both indoor and outdoor detection. Besides, it is capable of the quantized detection of droplet distribution, providing an effective way of tests for spray technique, especially for the research of the application of plant protection by UAVs.Keywords: droplets, distribution, detection, agricultural aviation, UAVDOI: 10. 25165/j.ijabe.20171004.3118Citation: Zheng Y J, Yang S H, Lan Y B, Hoffmann C, Zhao C J, Chen L P, et al. A novel detection method of spray droplet distribution based on LIDARs. Int J Agric & Biol Eng, 2017; 10(4): 54–65.